2021
DOI: 10.1155/2021/9483433
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Withania somnifera Modulating Antitumor Immunity in Targeting Prostate Cancer

Abstract: Medicinal plants serve as a lead source of bioactive compounds and have been an integral part of day-to-day life in treating various disease conditions since ancient times. Withaferin A (WFA), a bioactive ingredient of Withania somnifera, has been used for health and medicinal purposes for its adaptogenic, anti-inflammatory, and anticancer properties long before the published literature came into existence. Nearly 25% of pharmaceutical drugs are derived from medicinal plants, classified as dietary supplements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 101 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…In addition, the treatment led to the modulation of cyclinB1, PCNA, and p34, and altered the expression of p53-mediated apoptotic markers, such as Bcl-2, caspase-3, and PARP cleavage [ 95 ]. An oral dose of 3–5 mg/kg withaferin A attenuated the activation of Akt and stimulated Forkhead Box-O3a (FOXO3a)-mediated prostate apoptotic response-4 (Par-4) activation, effectively inhibiting the tumor progression in prostate cancer cells [ 96 , 97 , 98 ]. Several studies have also shown that colorectal adenocarcinoma cells treated with withaferin A significantly delay the mitotic cell cycle process by promoting the degradation of mitotic arrest deficiency 2 (Mad2), Cdc20, and the spindle assembly checkpoint (SAC) [ 99 ].…”
Section: Antineoplastic Regulation Of Cellular Processes In Different...mentioning
confidence: 99%
“…In addition, the treatment led to the modulation of cyclinB1, PCNA, and p34, and altered the expression of p53-mediated apoptotic markers, such as Bcl-2, caspase-3, and PARP cleavage [ 95 ]. An oral dose of 3–5 mg/kg withaferin A attenuated the activation of Akt and stimulated Forkhead Box-O3a (FOXO3a)-mediated prostate apoptotic response-4 (Par-4) activation, effectively inhibiting the tumor progression in prostate cancer cells [ 96 , 97 , 98 ]. Several studies have also shown that colorectal adenocarcinoma cells treated with withaferin A significantly delay the mitotic cell cycle process by promoting the degradation of mitotic arrest deficiency 2 (Mad2), Cdc20, and the spindle assembly checkpoint (SAC) [ 99 ].…”
Section: Antineoplastic Regulation Of Cellular Processes In Different...mentioning
confidence: 99%
“…In the realm of holistic health, it is often likened to ginseng for its stress-reducing capabilities, cognitive enhancements (e.g., memory improvement), and support for a robust immune system [ 21 ]. One of its remarkable features is its ability to modulate the immune system, striking a balance between the humoral and cellular responses of the adaptive immune system [ 22 ]. The therapeutic effects of W. somnifera are primarily attributed to its active constituents, including alkaloids, steroidal lactones (e.g., withanolides, withaferin A), and steroidal saponins [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%